Manajemen Madrasah dalam Perspektif Sejarah - Rini Setyaningsih (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
The Developing of madrassa from classical times to the present can not be treated partially or half-and-half, but requires thinking the development of a complete and comprehensive measures and efforts are visible, flexible and credible, especially when faced with the national development policy in education who have the vision of the educational system as a social institution that is strong and authoritative to empower all citizens of Indonesia develop into quality human, so capable and proactive answer the challenges of changing times (see explanation of Law No. 20/2003 on the National Education System). Plus era of globalization has given a wide impact in many aspects of life, including quality demands in the organization of education. In this era every field requires the Human Resources (HR) qualified high caliber and reliable, so competition especially concerning human resources are very tight. to meet this demand, the improvement and development of education provision in each madrasah system continuously needs to be done in line with the dynamic development of science as well as the dynamics of change in society itself that is the development of character concerning the aspects of soft skills (spirituality) and hard skills (intellect). Strengthening way blend of character development in the stretcher build madrassas ideals and a strong academic culture that lead to superior output and good as expected madrasah in this age of globalization. Surely madrasas must have good managerial system in realizing the goal of madrasa education in it self.